The silent roar a decade of change - Raja Petra Kamarudin 1950- (Argyll Publishers, 2009)
"Compiled from RPK's popular website, Malaysia Today, "The Silent Roar" is not only a compilation of selected articles, commentaries and essays on unfolding developments and issues in Malaysia, it also features new and unpublished writings exclusive to this publication" -- Back cover.